Do hospitals earn their nonprofit status? Evidence from New Hampshire in 2012. Issue 1 (5th March 2018) - Plante, Catherine; Ragland, Linda
Abstract : Purpose: The purpose of this paper is to add to the stream of research examining the difference between the amount of taxes waived for nonprofit hospitals and the amount of charity care they provide. Design/methodology/approach: The study is an archival study. Findings: Almost all nonprofit hospitals in the sample provide enough charity care to cover their waived taxes. Almost none provide enough charity care at the level that has been proposed to the federal government for hospitals to maintain their nonprofit status. Research limitations/implications: As with most hospital research, a limitation is this study's focus on a single state to control for regulatory differences among states. Practical implications: The data on the new Form 990 allow better measurement and transparency regarding a nonprofit hospital's charity care. For legislators, regulators, and taxpayers, the results from this study raise questions about: the large variations in the amount of charity care provided among nonprofit hospitals and whether enough is being done in terms of providing charity care. Social implications: There is great variation among nonprofit hospitals as to the amount of charity care provided. Relying upon a nonprofit hospital's altruistic nature may not be enough to ensure that they act in the best interest of society. Originality/value: This study is unique because, for the first time, a true measure of taxes waived is used in the analysis. All previous research has had to proxy taxes.